MICROSCOPIC AND MOLECULAR DIAGNOSIS OF Ascaridia spp. IN DOMESTIC PIGEONS(Columba livia domestica) IN BAGHDAD CITY,IRAQ - & Al- Amery, Faraj (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
Ascaridiosis is a very important parasitic disease of birds, it is caused by Ascaridia. This study was conducted to identify the Ascaridia species by microscopic and molecular assay in Baghdad city. One hundred and sixty fecal samples were collected from domestic pigeons during the period from 1/1/ 2019 to 31/3/ 2019.  Results showed that the rate of infection for Ascaridia spp. 15.62% by microscopic examination.  Significant difference was observed in infection rates between males and females pigeons. Fifty samples randomly selected and subjected to molecular diagnosis of Ascaridia  spp.. Molecular examination results, the total infection rate showed 16%(8/50). The eight  positive PCR products were sequenced and deposited in Gene bank data base, phylogenic analysis demonstrated that 4 sequences belongs to Ascaridia galli ( MK918635.1, MK918636.1, MK918847.1, MK919081.1), while 2 (MK919199.1, MK919200.1) belong to  Ascaridia nymphii and 2 (MK919207.1, MK919264.1)  belong to Ascaridia numidae. It is the first study in Iraq to diagnosis of  Ascaridia nymphii and Ascaridia numidae  in domesticed pigeons by using conventional PCR.